2022
DOI: 10.3390/proteomes10030027
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in Team-Sport Athletes: Current Knowledge, Challenges, and Future Perspectives

Abstract: Metabolomics is a promising tool for studying exercise physiology and exercise-associated metabolism. It has recently been defined with the term “sportomics” due to metabolomics’ capability to characterize several metabolites in several biological samples simultaneously. This narrative review on exercise metabolomics provides an initial and brief overview of the different metabolomics technologies, sample collection, and further processing steps employed for sport. It also discusses the data analysis and its b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Adherence to nutritional guidelines for both match-day and post-match recovery, and the standardization of training loads are key for achieving this goal ( Mohr et al, 2016 ). These studies would also benefit from evaluating non-invasive samples such as saliva and urine to improve the applicability to real-world conditions ( Bongiovanni et al, 2022 ). Additionally, systematic analyses have shown that sex plays an important role in driving differences in metabolomic profiles, thus representing an important factor to consider in football studies ( Costanzo et al, 2022 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Adherence to nutritional guidelines for both match-day and post-match recovery, and the standardization of training loads are key for achieving this goal ( Mohr et al, 2016 ). These studies would also benefit from evaluating non-invasive samples such as saliva and urine to improve the applicability to real-world conditions ( Bongiovanni et al, 2022 ). Additionally, systematic analyses have shown that sex plays an important role in driving differences in metabolomic profiles, thus representing an important factor to consider in football studies ( Costanzo et al, 2022 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Metabolomics, a facet of 'omics' science that extensively measures small metabolites in biological samples, has become increasingly prominent in sports medicine (15,34). Termed "sportomics," this approach is crucial in studying exercise physiology and metabolism.…”
Section: Use Of Big Data In Metabolomicsmentioning
confidence: 99%
“…Termed "sportomics," this approach is crucial in studying exercise physiology and metabolism. The integration of big data in metabolomics is significantly enhancing our comprehension of athletes' physiological responses to exercise (34).…”
Section: Use Of Big Data In Metabolomicsmentioning
confidence: 99%
“…Exercise can potentially impact the human metabolome ( 1 , 2 ). The application of “-Omics” sciences in the field of play of various sports was conceived as sportomics, aiming to investigate the real challenges athletes face, using sports as a model of metabolic stress ( 3 , 4 ). Sportomics, like all “-Omics” sciences, depends on analytical methods with high processing power to analyze massive volumes of data and is a promising field of investigation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%